2020
DOI: 10.1002/best.202000012
|View full text |Cite
|
Sign up to set email alerts
|

Biegeverstärkung mit Carbonbeton

Abstract: Bestehende Stahlbetonkonstruktionen können mit einer Vielzahl an Systemen instand gesetzt bzw. verstärkt werden, wobei zu den gebräuchlichsten Methoden eine Verstärkung mit Spritzbeton oder mit Lamellen aus faserverstärkten Kunstoffen (FVK) gehört. In den vergangenen Jahren hat sich mit Textilbeton eine weitere Möglichkeit entwickelt, bei der es sich um eine dünne, leistungsfähige Verstärkungsschicht aus einem Feinbeton handelt, welche mit einem textilen Gelege bewehrt ist. Die Dicke einer solchen Schicht betr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 17 publications
0
13
0
1
Order By: Relevance
“…The experimental and theoretical investigations were done in a collaborative research effort of the Technical Universities of Dresden and Darmstadt (Germany). The production process of the RC members as well as the experimental investigations under short-term loading are well reported in Müller et al 4 The test setup, cross-sectional dimensions and the reinforcement layout are shown in Figure 1.…”
Section: Test Setup and Materials Properties 21 | Test Specimens And ...mentioning
confidence: 86%
See 4 more Smart Citations
“…The experimental and theoretical investigations were done in a collaborative research effort of the Technical Universities of Dresden and Darmstadt (Germany). The production process of the RC members as well as the experimental investigations under short-term loading are well reported in Müller et al 4 The test setup, cross-sectional dimensions and the reinforcement layout are shown in Figure 1.…”
Section: Test Setup and Materials Properties 21 | Test Specimens And ...mentioning
confidence: 86%
“…In Figure 13B, the ultimate loads of the reference tests and the residual strength tests are shown. The load‐bearing capacities of the unreinforced members reported in Müller et al, 4 yield to a mean value of approximately F max,RU,m = 19.2 kN ( M max,RU,m = 7.2 kNm) compared with a value of F max,RS,m = 92.2 kN ( M max,RS,m = 34.6 kNm) for the strengthened members. The latter is in good agreement with the calculation in Section 3.1 and is approximately 7% higher.…”
Section: Experimental Investigationsmentioning
confidence: 88%
See 3 more Smart Citations